Dinamika Pesantren: Studi Futuristic Transformasi-Tansmisi Sistem Pesantren di Mandailing Natal - Suryadi Nasution; Muhammad Ikbal; Ali Jusri Pohan (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
This research aimed to re-reduce the system of Pesantren (islamic boarding school) in Mandailing Natal and then formulating the direction of transformation and transmission of Pesantren after the issuance of the Pesantren Law No. 18 of 2019. The methodological practice in this investigation was qualitative with the concept of a need assessment to explore the reality and ideals standards which were set in the derivatives of the law, especially in terms of the formal education system in pesantren, curriculum content, student management, and pesantrens' infrastructure in Mandailing Natal. while the data analysis used was structured based on the criteria for Pesantren Muadalah System and Formal Diniyah Education (PDF). The results showed that the majority of Pesantren in Mandailing Natal did the installation of Madrasah to the pesantren system in order to ensure the continuity of graduates continuing towards higher education, where pesantren having two lines of coordination at once, namely Penmad and PD Pontren Kemenag. In fact, the pesantren in Mandailing Natal got ready for a system transformation to Pesantren Muadalah or PDF since it had fullfilled all the required aspects, such as the number of students who were more than 250, the existence of curriculum of " kitab kuning", the readiness of human resources, and the availability of supporting infrastructure.